Bifunctional catalytic PVA composites for the one pot synthesis of camphor from camphene - Castanheiro, J (2012)
The preparation of bifunctional catalysts consisting of PVA containing sulfonic groups and redox functions corresponding to Co(acac)2 occluded in the polymer or encapsulated in zeolite Y dispersed in the polymer matrix, is reported. The catalysts are used in the one pot synthesis of camphor from camphene.